2008
DOI: 10.1044/1058-0360(2008/012)
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Microstructure of Written Language Using a Retelling Paradigm

Abstract: Clinicians can use this multidimensional scheme for examining writing skills using text-retelling formats with children from Grades 3 through 6. This empirically based framework for measuring microstructural variables of writing provides clinicians with a 3-prong conceptual framework for determining children's strengths and weaknesses within the translational stage of writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
109
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 46 publications
19
109
1
2
Order By: Relevance
“…Moreover, it was recently reported that the syntactic complexity of sentences produced by a group of third graders with poor transcription skills was significantly lower than those produced by an aged-matched group but equivalent to transcription matched group of first graders (García, Crespo, & Bermúdez, 2016). Correlational evidence also suggested that, at least in school-aged writers, higher TRANSCRIPTION-WRITING LINK 9 transcription skills are associated with higher syntactic skills (Berninger et al, 2011;Kim, Al Otaiba, Wanzek, & Gatlin, 2014;Puranik, Lombardino, & Altmann, 2008;Wagner et al, 2011).…”
Section: Transcription Constrains Planning and Translatingmentioning
confidence: 87%
“…Moreover, it was recently reported that the syntactic complexity of sentences produced by a group of third graders with poor transcription skills was significantly lower than those produced by an aged-matched group but equivalent to transcription matched group of first graders (García, Crespo, & Bermúdez, 2016). Correlational evidence also suggested that, at least in school-aged writers, higher TRANSCRIPTION-WRITING LINK 9 transcription skills are associated with higher syntactic skills (Berninger et al, 2011;Kim, Al Otaiba, Wanzek, & Gatlin, 2014;Puranik, Lombardino, & Altmann, 2008;Wagner et al, 2011).…”
Section: Transcription Constrains Planning and Translatingmentioning
confidence: 87%
“…The analysis according to grades showed similar performances of 4 th and 5 th grades, and between 6 th and 7 th grades, being the occurrence of essential macrostructures higher in more advanced grades. In fact, the literature indicates that there is a progression in writing narratives with increasing education, i.e., the ability to elaborate written constructions receives positive influence of formal and systematic education (26,29).…”
Section: Discussionmentioning
confidence: 99%
“…During childhood, syntax skills have been shown to develop quite slowly (Puranik et al, 2008;Scott, 1988) with very little difference between grades. If syntax is slow to develop, it may also require a longer intervention period in order to affect a stable change.…”
Section: Sample Sizementioning
confidence: 99%
“…Given that syntactic skills are still in the process o f developing during the school years (Puranik et al, 2008;Scott, 1988), fluctuations in syntactic productions and conjunction use should be expected. Such fluctuations would account for the inconsistencies found for the syntactic treatments, and suggest that, the associative networks that govern complex sentence structures and conjunction use may not yet be strong enough to outweigh the contributions of semantic processing.…”
Section: Text G Eneration Revisitedmentioning
confidence: 99%
See 1 more Smart Citation